Luogo E Segni : Punta Della Dogana - Bethenod, Martin; Mekouar, Mouna (Venezia : Marsilio, 2019)
Adnan, Etel ; Abbott, Berenice ; Anselmo, Giovanni ; Arruda, Lucas ; Berrada, Hicham ; Boutros, Charbel-Joseph H. ; Brancusi, Constantin ; Canell, Nina ; Dean, Tacita ; Deschenes, Liz ; Fattal, Simone ; Dekyndt, Édith ; Gonealez-Foerster, Dominique ; Gonzalez-Torres, Felix ; Horn, Roni ; Janssens, Ann Veronica ; Lozano, Lee ; Martin, Agnes ; Mehretu, Julie ; Parreno, Philippe ; Piangiamore, Alessandro et al.
Luogo E Segni, Punta Della Dogana, Palazzo Grassi, Pinault Collection, Venezia, 25 mars - 12 décembre 2019
boek